Kepatuhan Minum Obat Pencegahan Filariasis di Wilayah Kerja Puskesmas Waihaong dan Air Salobar Kota Ambon - Iwan, Ressita Fannia; Titaley, Christiana Rialine; Taihuttu, Yuniasih; Krentel, Alison (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Lymphatic Filariasis (LF) is an infectious disease caused by filarial worms and transmitted by mosquitoes. Mass drug administration (MDA) for LF is used in endemic areas to stop transmission and prevent disability due to LF. This study aims to identify factors associated with overall compliance with the MDA in 2018 in the catchment areas of Waihaong and Air Salobar Health Centers, Ambon. Method: This analysis used data derived from a survey conducted by the Faculty of Medicine Pattimura University, Ambon, in January 2019. We used information from 745 subjects who received LF drugs in both study areas. Logistic regression analysis was employed to determine factors associated with community compliance with taking filariasis drugs. Results: Our study found that only 67% of the community swallowed LF drugs (60,3% in Waihaong and 72,6% in Air Salobar). Higher compliance with swallowing the LF drugs was found in respondents living in the catchment area of Air Salobar Health Center (OR=2,01, 95%CI:1,42-2,86, P-value<0,001);with a high level of knowledge (OR=1,91, 95%CI:1,34-2,74, P-value<0,001 and with a high sense of trust towards the drugs deliverers (OR=4,93, 95%CI:2,17-11,22, Pvalue<0,001). Furthermore, respondents who felt a high moral obligation to take the drugs (OR=2,39, 95%CI:1,15-4,94, P-value=0,019); and received social support to take the drugs (OR=5,12, 95%CI:3,18-8,23, P-value<0,001) were also more likely to comply with treatment. This study shows that health promotion interventions to increase community awareness and knowledge are still required in Ambon City despite many rounds of mass drug administration. Various educational media and efforts to increase knowledge and capabilities of the drug deliverers are essential to improve community compliance with taking LF drugs.